CHALLENGES IN MEXICAN HIGHER MUSICAL TRAINING - Cavazos Guerrero, Patricia Ivonne; Marroquín Narváez, Graciela Mirna (Atenas, 2013)
In the higher musical training it is necessary to consider the fact that parents and their attitudes towards their children´s studies influence directly on the fulfillment of academic objectives. Aiming at the knowledge of the present paradigm in the musical career and its impact on the results of students from the UANL Music Faculty, we decided to explore one of the factors that, according to Adell, (Adell, 2006), affect this paradigm: the family dimension. We gave an anonymous survey to 20, 45 5 of the student population to know the perception that students have about the variables of support that they get from their parents (moral, material and economic). Because Mexico is a developing country, the social paradigm ruling in the music career in Nuevo León, affects negatively the academic rendering, so for the students it represents an extra challenge due to the lack of familiar support. As an strategy to solve this we used tutoring as a tool that favors communication and the relation professor-student-family.